2021
DOI: 10.1200/jco.20.01632
|View full text |Cite|
|
Sign up to set email alerts
|

Mutant Isocitrate Dehydrogenase 1 Inhibitor Ivosidenib in Combination With Azacitidine for Newly Diagnosed Acute Myeloid Leukemia

Abstract: PURPOSE Ivosidenib is an oral inhibitor of the mutant isocitrate dehydrogenase 1 (IDH1) enzyme, approved for treatment of IDH1-mutant (m IDH1) acute myeloid leukemia (AML). Preclinical work suggested that addition of azacitidine to ivosidenib enhances mIDH1 inhibition–related differentiation and apoptosis. PATIENTS AND METHODS This was an open-label, multicenter, phase Ib trial comprising dose-finding and expansion stages to evaluate safety and efficacy of combining oral ivosidenib 500 mg once daily continuous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 133 publications
(94 citation statements)
references
References 28 publications
2
90
1
1
Order By: Relevance
“…Although the ivosidenib/azacitidine combination could be safely administered in an outpatient setting, more than half of the patients required hospitalizations related to AEs. However, the number of hospitalization days per patient-year of drug exposure owing to AEs in this study was encouragingly lower than that previously reported for azacitidine monotherapy (43).…”
Section: Adverse Events and Safety In Patients Treated With Ivosidenibcontrasting
confidence: 68%
See 1 more Smart Citation
“…Although the ivosidenib/azacitidine combination could be safely administered in an outpatient setting, more than half of the patients required hospitalizations related to AEs. However, the number of hospitalization days per patient-year of drug exposure owing to AEs in this study was encouragingly lower than that previously reported for azacitidine monotherapy (43).…”
Section: Adverse Events and Safety In Patients Treated With Ivosidenibcontrasting
confidence: 68%
“…Median OS has not been reached with a 12-month survival estimate of 82.0% (95% CI, 58.8% to 92.8%). mIDH1 clearance in bone marrow mononuclear cells by BEAMing (beads, emulsion, amplification, magnetics) digital polymerase chain reaction with a sensitivity of 10 -4 (60) was seen in 10/14 patients (71.4%) achieving CR (43).…”
Section: Enasidenib and Ivosidenib As Part Of Multi-agents Regimensmentioning
confidence: 99%
“…A small phase 1/2 study of ivosidenib in combination with azacitidine in newly diagnosed AML showed a response rate of 78.3% that was durable. 19 Patients who achieved a CR had a high clearance rate of IDH1 mutation (71.4%). In the same trial, IDH2 -mutated AML patients were enrolled and treated with the combination of enasidenib and azacitidine.…”
Section: Targeting Idh Mutations By Small Molecule Idh Inhibitorsmentioning
confidence: 99%
“…Pre-clinical investigation of mutant IDH1 transformed cell lines demonstrated enhanced differentiation and apoptosis with the combination of azacytidine and ivosidenib (Yen, Cancer Res 78;2018 suppl; abstr 4956). This led to a Phase 1b clinical trial which enrolled 23 patients to the combination of azacytidine and ivosidenib, demonstrating a CR rate of 61%, CR/CRh rate of 70%, and a 12-month OS of 82% (median duration of response or DOR has not been reached, with median follow-up of 16 months) 30 . The follow-up confirmatory Phase 3 AGILE study of ivosidenib vs placebo in combination with azacytidine in untreated AML is now ongoing (NCT 03173248) with a primary endpoint of relapse-free survival.…”
Section: Targeting Idh2 In Amlmentioning
confidence: 99%